Gambaran Umum dan Tata Laksana Kalazion - Lintang Lestari Cahya Sawitri; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Chalazion is the most common local inflammatory condition, accounting for 13.4% of all benign eyelid lesions, caused by obstruction of the meibomian glands in the upper or lower lid, either unilaterally or bilaterally. Chalazion is a chronic granulomatous inflammatory condition of the Meibomian glands which are responsible for producing meibum which can reduce tear evaporation and facilitate lubrication of the ocular surface. This situation is often associated with acne rosacea, atopy, seborrheic, and chronic blepharitis. The lesions are inflammatory nodules that form when the products of lipid breakdown enter the surrounding tissue and trigger a granulomatous inflammatory reaction. The nodule is not more than 1 cm in size, not hyperemic, not painful when pressed, not fluctuate, and pseudoptosis. Single hard textured nodule located deep in the upper or lower lid or tarsal. Management can be done through a conservative approach, antibiotics, and surgery. Conservative medical treatments include warm compresses, eyelid massage, eyelid scrubs, and eyelid cleansing with baby shampoo. Antibiotics are generally not indicated, unless the condition is associated with severe blepharitis or blepharitis due to rosacea. Persistent lesions require surgical intervention. Smaller lesions are treated by surgical curettage and dissection. Larger lesions require more extensive excision. Good sleeping habits, regular exercise, and fresh air are essential to promote healthy skin and Meibomian glands.